2017
DOI: 10.36076/ppj.2017.e591
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose and Procedure Time for 994 CT-guided Spine Pain Control Procedures

Abstract: Background: Image guidance for spine pain control procedures, including epidural steroid injection, nerve root block, and facet block, can be performed with either computed tomography (CT) or conventional fluoroscopy. CT has the advantage of improved anatomic localization and use of air for contrast; however, there are concerns that CT leads to higher radiation dose and longer procedure time. Objective: To evaluate procedure time and radiation dose for multiple types of spine pain control procedures performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…11 With safety and efficacy equivalence, this study suggests that CF is the more practical technique by way of potentially reduced procedural times and radiation exposure for both the patient and the proceduralist. 11,21,25,27 Nevertheless, there is a recent publication by Dietrich et al 28 that suggests that radiation exposure for the proceduralist may be higher with CF than with CT/F-guided lumbar procedures. However, the authors indicated that during most CT/F acquisitions, the proceduralist is positioned behind the side of the gantry, while during most acquisitions with CF guidance, the operator is directly adjacent to the patient.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…11 With safety and efficacy equivalence, this study suggests that CF is the more practical technique by way of potentially reduced procedural times and radiation exposure for both the patient and the proceduralist. 11,21,25,27 Nevertheless, there is a recent publication by Dietrich et al 28 that suggests that radiation exposure for the proceduralist may be higher with CF than with CT/F-guided lumbar procedures. However, the authors indicated that during most CT/F acquisitions, the proceduralist is positioned behind the side of the gantry, while during most acquisitions with CF guidance, the operator is directly adjacent to the patient.…”
Section: Discussionmentioning
confidence: 83%
“…All fluoroscopy times for CF-SCNRB were recorded at under 2 minutes, with a range of 7-78 seconds. The fluoroscopy time averaged 24.3 seconds per procedure, and radiation exposure based on the time is shown in Table 4 and compared with an average effective dose for CT-guided interventions in a study by Lazarus et al 11 using a conversion factor developed by Huda et al 21…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations